Serological Markers in the Prognosis of the Development of Human Speed Abilities - Valentyna Lyshevska; Serhiy Shepoval (Lesya Ukrainka Volyn National University, 2018)
The article presents data on the study of a correlation between blood groups system AB0 and Rh with the peculiarities of the development of human speed abilities. It identifies a complex of genetic markers and substantiates the possibility of using this complex in the individual prognosis of the development of human motor abilities. The study shows that individuals with 0(I) and A(II) blood groups and Rh+ have a high predisposition to the development of speed abilities.